LABOR LAW PROTECTION OF WORKERS WHO CARE FOR ELDERLY FAMILY MEMBERS - Gvero, Sanda (Zbornik radova Pravnog fakulteta u Novom Sadu, 2025)
The paper analyzes the legal position of workers who care for older family members, with a special focus on the possibilities and limitations of their labour law protection. Starting from the process of demographic ageing and the growing need for other people’s care and assistance, it points out the increasingly present multiple obligations of workers - in professional and family life - as well as the consequences that the absence of systemic support produces on the personal, social and economic level. Comparative legal analysis shows that there is no universal solution, but some countries offer innovative models of support, which include special forms of leave, flexible working arrangements and financial compensation. The author points to the need to introduce similar measures into the domestic legal system, as well as the necessity of recognizing informal caregivers as a special category in law. The protection of caregivers reflects not only concern for the individual, but also a vision of a socially responsible and functional legal order.